Litterfall and nutrient transfer dynamics in a successional gradient of tropical dry forest in Colombia - Montañez-S, Angie (2023)
Introduction: The litterfall production, foliar nutrient dynamics and decomposition are essential to maintain nutrient cycling, soil fertility, and carbon regulation in terrestrial ecosystems. With several studies addressing the variation of these processes, their dynamics in tropical dry forests (TDFs) remain unclear, due to its complex interaction of biotic and abiotic factors. Objective: To evaluate litterfall, nutrient potential return and use efficiency, and decomposition variation in a TDF successional gradient in Tolima, Colombia. Methods: We quantified litterfall from November 2017 to October 2019 in 12 plots distributed in four successional stages: initial, early, intermediate, and late forests. We identified key tree species in foliar litter production and characterized the foliar decomposition of these species. At the community level, we quantified the C, N and P potential return, the N and P use efficiency, and the C:N and N:P ratio. Subsequently, we analyze relationships between vegetation characteristics and some soil chemical properties with these ecological processes. Results: We found that total litterfall in late forests (8.46 Mg ha-1 y-1) was double that found in initial forests (4.45 Mg ha-1 y-1). Decomposition was higher in initial (k = 1.28) compared to intermediate (k = 0.97) and late forests (k = 0.87). The nutrient potential return didn’t change along succession, but it did show differences between study sites. The structural development and species richness favored litterfall, while soil chemical conditions influenced nutrient returns and decomposition. Conclusions: TDFs could recover key ecosystem function related to litterfall and nutrient dynamics after disturbances cessation; however, the soil quality is fundamental in return and release of nutrients.